Influence of personality, attitude, motivation, and environment on the entrepreneurial spirit of school cooperative teachers in vocational schools in Kulon Progo regency - Triatun, Triatun; Sukidjo, Sukidjo (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
This study aims to determine the influence of personality, attitude, motivation, and environment on the entrepreneurial spirit both partially and simultaneously. The research method uses a survey with 39 teachers of school cooperatives and respondents numbering 33 people. Primary data was obtained using questionnaires supported by observations and interviews on cooperative teachers and related parties: data analysis using descriptive statistics and multiple regressions with t-test and F tests. The results showed that personality, attitude, motivation, and the environment simultaneously and partially influenced positively and significantly the entrepreneurial spirit. The four variables contributed to the entrepreneurial spirit by 80.30%, while factors outside the research influenced 19.70%. The environment is the variable that contributes the most to the entrepreneurial spirit with a percentage of 23.52%, followed by personality by 20.91%, motivation 19.88%, and attitude 15.99%.